2023
DOI: 10.1002/rcm.9461
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography coupled to time‐of‐flight mass spectrometry using parallel electron and chemical ionization with permeation tube facilitated reagent ion control for material emission analysis

Abstract: Rationale: Volatile organic compounds (VOCs) emitted by an artificial leather part for car interiors are determined using GC-MS (gas chromatograph coupled to a mass spectrometer) using simultaneous electron and chemical ionization (EI&CI). A device for swift reagent ion switching in CI mode between consecutive runs is presented. Methods: VOCs emitted from the investigated material were sampled onto Tenax ® absorption tubes using micro emission chambers and subsequently injected into the GC through thermal deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Especially at high retention time, many alkylbenzenes eluted (see SI Table S2), which are not ionizable by [NH 4 ] + . However, [NH 4 ] + may improve the precursor ion yield for very fragile compounds, as previously presented by Brakling et al, 20 and enhances the identification if the Applying the identification confidence levels by Schymanski et al, 29 6% of the compound identities were confirmed with a reference standard (level 1), for 41% a structure was proposed (level 2a and b), for 24% a tentative structure was proposed (level 3), for 29% a molecular formula was stated (level 4) and for 4% only the accurate mass could be gained (level 5) (see Figure 5G). However, for level 2, an identification confirmation by RI was necessary, which originally was not included by Schymanski et al, as the workflow was developed for LC-based methods.…”
Section: Gc-eiandci-tofms Analysismentioning
confidence: 74%
See 3 more Smart Citations
“…Especially at high retention time, many alkylbenzenes eluted (see SI Table S2), which are not ionizable by [NH 4 ] + . However, [NH 4 ] + may improve the precursor ion yield for very fragile compounds, as previously presented by Brakling et al, 20 and enhances the identification if the Applying the identification confidence levels by Schymanski et al, 29 6% of the compound identities were confirmed with a reference standard (level 1), for 41% a structure was proposed (level 2a and b), for 24% a tentative structure was proposed (level 3), for 29% a molecular formula was stated (level 4) and for 4% only the accurate mass could be gained (level 5) (see Figure 5G). However, for level 2, an identification confirmation by RI was necessary, which originally was not included by Schymanski et al, as the workflow was developed for LC-based methods.…”
Section: Gc-eiandci-tofms Analysismentioning
confidence: 74%
“…Especially at high retention time, many alkylbenzenes eluted (see SI Table S2), which are not ionizable by [NH 4 ] + . However, [NH 4 ] + may improve the precursor ion yield for very fragile compounds, as previously presented by Bräkling et al, and enhances the identification if the precursor ion shows a low abundance with protonation reaction CI reagents or if the resulting ions of other reagents can not be unequivocally assigned to a molecular structure. The overall coverage of accurate mass precursor ion information is ∼86%, which highlights the advantage of using three different CI reagents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Semi-targeted metabolomics assessed the plasma levels of 74 metabolites involved in carbohydrates, amino acids, lipids, cofactors, vitamins, nucleotide pathways, energy metabolism, and xenobiotic biodegradation [20,21]. Plasma samples (50 μL) were mixed with an 8:2 (v/v) methanol: water solution containing internal standards, vortexed, and centrifuged.…”
Section: Methodsmentioning
confidence: 99%